The Relevance of the Practice of Ifá Divination in Ola Rotimi’s The Gods are not to Blame - Olusegun Olu-Osayomi; Babatunde Adebua (Yoruba Studies Review)
The custom of Ifá divination is common among the Yorùbá of Western Nigeria, and among Africans generally. This paper attempts an evaluation of the relevance of the practice of Ifá divination in the selected play of Ola Rotimi to Yorùbá culture and metaphysics. This is purposely to attain a greater and more profound awareness of its role as a symbol of communal and cultural identicalness. Using The God Are Not to Blame (1975) as an illustration, the paper contends, in a poignant manner, that the elements of Yorùbá Ifá divination, through oracular devices, well manifested in the structuring principles of Rotimi’s work. This is analyzed from spiritual and mythological angles. With an overwhelming lucidity, the paper posits that actions in the play are influenced by an assumption that any collective catastrophe or adversities are the outcomes of disharmony between disparate cosmos. The aforementioned includes a detailed interrogation of the rationality and logic of these beliefs as Rotimi presents them. Through the ambiance of the various events in the play, the paper establishes that the practice of Ifá divination in Yorùbá land is not only a way of life but has also transcended traditional, Christian, and Muslim traditions and beliefs. Finally, while recognizing the enduring popularity and artistic forte of Rotimi’s magnum opus, the paper broadens spasmodically our perception of the pervasiveness and practical relevance of the practice of Ifá divination as means for rectifying evil destiny, regulating what the future holds and resolving problems of existence in Yorùbá culture and metaphysics.